POVERTY AND UNEMPLOYMENT DUE TO COVID-19 IN BALUMBUNG VILLAGE, KEC. TOMPOBULU, KAB. BANTAENG - Firdayanti J. Umar; Sam’un Mukramin (Media Inovasi Pendidikan dan Publikasi, 2023)
This article discusses the increase in the unemployment rate. Unemployment is also related to the availability of jobs, the availability of jobs is related to investment, while investment can be obtained from accumulated savings, savings are the rest of income that is not consumed. The higher the national income, the greater the hope for the opening of new production capacity which of course will absorb new workers (Purba et al., 2022) the term of unemployment for people who do not work at all, are looking for work, work less than two days for a week, or someone who is trying to get a job (According to the Central Bureau of Statistics) (Lincolyn, 2005). Unemployment is a factor of poverty that exists in society, due to the lack of jobs for them to earn income to meet their daily needs. The absence of equal distribution of employment opportunities is also the cause of quite a lot of unemployment, Indonesia is one of the countries that has a lot of unemployment, lagging behind technological developments makes it difficult to open jobs. Job opportunities are the number of people who can be accommodated to work in a company to fulfill or get available jobs (Arif Novriansyah, 2018). The country of Indonesia, which incidentally is a developing country, certainly has its own challenges to overcome this unemployment problem. Unemployment in this case is a main or main problem that is felt by all developing countries, unemployment is a condition for the age of the workforce in the range of 15-65 years who are not working or are looking for work (Yoga, 2021). People who are not currently looking for work, for example, are housewives, junior high school students, high school students, college students, and others because they don't need a job yet. However, unemployment is not limited, which in this case means someone who does not have a job, is applying for or looking for a job position (Mifrahi & Darmawan, 2022). Every day the number of COVID-19 cases in Indonesia is increasing. The increase in cases caused the government to implement a new policy, known as Large-Scale Social Restrictions (PSBB). This PSBB policy is implemented in several regions of Indonesia which have experienced the highest cases of COVID-19, such as the Jakarta Region. (Indayani & Hartono, 2020)